<span>A) y=-2x+19
B) y=x+7
Multiplying B) by -1
B) -y = -x -7 then adding it to A)
A) y = -2x + 19
3x = 12
x = 4
y = 11
</span>
Let's solve for x --
Isn't it always a little easier to solve a math problem with starting by rewriting the equation?
3/8x + 15/2 = 8
Step 1) Subtract 15/2 from both sides
3/8x + 15/2 - 15/2 = 8 - 15/2
3/8x = 1/2
Step 2) Multiply both sides by 8/3
(8/3) × (3/8x) = (8/3) × (1/2)
x = 4/3
FINAL ANSWER -
x = 4/3
↑ ↑ ↑ Hope this helps! :D
Answer:
B
Step-by-step explanation:
Answer:
(58-11) divided by 20
Step-by-step explanation:
Answer:
<h2>x = 2</h2>
Step-by-step explanation:
3 - x + 1 = 2 <em>combine like terms</em>
-x + (3 + 1) = 2
-x + 4 = 2 <em>subtract 4 from both sides</em>
-x +4 - 4 = 2 - 4
-x = -2 <em>change the signs</em>
x = 2